ANALISIS PENGARUII CURAH HUJAN, SUIIU UDARA DAN KELEMBABAN UDARA TERHADAP PRODUKSI JAGUNG DI KABUPATEN LANGKAT - Natal Ginting; Retna Astuti Kuswardani; Azwana Azwana (JURNAL AGRICA, 2018)
Corn is a food that referred the most essential after rice in the lives of people in Indonesia. In addition to human consumption, corn is also an ingredient for the production of animal feed that was active when the noodles into agribusiness mover. However, the issue of development of maize production in Indonesia is still importing noodles and outside negeni to meet domestic needs. Factors Natural Resources (SDA) and the weather elements such as precipitation, air temperature and humidity play a role in influencing the level of productivity of maize.The purpose of the study was to determine the extent of precipitation , air temperature and humidity affect the productivity of maize in the district of Langkat. The benefit is as a source of information and economic development of the agricultural sector, to increase farmers' income and GDP corn Langkat through more effective management system den efficiently on natural resources , weather and climate.Rainfall is ideal for corn is between 100-200 mm per month with distnibusi evenly. Growth of corn plants so the response to sunlight and moisture content in the atmosphere . The combination of weather factors between rainfall, air temperature and humidity ideal will lead to increased productivity of maize over the maximum.Sources of data were taken and the Department of Agriculture Langkat , the Central Statistics Agency (BPS) Langkat, Sampali Climatological Station and Office Center for Meteorology and Geophysics Region I Field. Processing methods with the computer program SPSS version 19 using analysis regeresi linear equations, test "F", test "t", the coefficient of determination R2 and significant . The analysis showed that rainfall , air temperature and humidity have a significant effect on the level of productivity of maize in the region Langkat. Keywords : Elements of weather and productivity of corn.